Jump starting self-employment? evidence among welfare participants in Argentina - Rita K. Almeida; Emanuela Galasso (Institute for the Study of Labor (IZA), 2007)
One important concern of governments in developing countries is on how to phase-out large safety nets programs. This paper evaluates the short run effects of one possible exit strategy, programs that promote self-employment, in Argentina. We provide evidence that a small fraction of beneficiaries were attracted by this program. Overall, potential participants to self-employment are more likely to be female household heads and more educated beneficiaries relative to the average Jefes beneficiaries. Using non-experimental methods, we show that participation in the program does affect labor supply of participants, by reducing the probability of having an outside job especially for males and increasing the total number of hours worked. However, the intervention fails to produce on average income gains to participating individuals and households in the short run. The fact that a very small subset of former welfare beneficiaries are attracted to the program, coupled with the fact that only a subset of participants (younger and more educated beneficiaries, and with previous self-employment experience) has important implications for this intervention to represent a viable exit strategy from welfare.
Keywords: 330; Selbstständige; Aktivierende Sozialhilfe; Argentinien